KOMUNIKASI DAKWAH IMAM AL-GHAZALI DALAM KITAB IḤYĀ ‘ULUMIDDĪN - Pia Khoirotun Nisa (STIT AL-AMIN KREO TANGERANG, 2018)
Dakwah communication of Imam al-Ghazali in his book Ihya Ulumuddin explains about the understanding of dakwah briefly and clearly. The book stresses to internalization process, diffusion, institutionalization and transformation of Islamic teaching that involves some aspects for realizing good life, safety and light in the world and in the world after here.